Implementasi strategi Problem-Based Learning dalam pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Al-Muttaqin Patrang Jember Tahun Pelajaran 2017/2018 - Efendi, Alek (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
The learning process should be organized in an interactive, fun, so that students can participate actively. such learning can be realized by using a scientific approach. In its application can use Learning strategy. SMP Al-Muttaqin Patrang Jember has implemented of Problem Based Learning in the learning of Islamic Education and Character. The purpose of this research is to describe the Planning, Implementation and Assessment of Problem-Based Learning Strategy in learning Islamic Education and Character in SMP Al-Muttaqin Patrang Jember School Year 2017/2018. The results of the implementation of the Problem-Based Learning (PBL) strategy in the learning of Islamic Religion and Budi Pekerti at Al-Muttaqin Junior High School Patrang Jember showed that: 1) planning was carried out at the beginning of each school year; those involved in planning activities are Head master, students of the curriculum and subject teachers; the development of learning devices independently; all teachers submit learning device including PAI teachers and Characteristics. 2) The implementation of learning, the teacher presents a problem that must be observed by students. then students formulate questions and collect information, then students discuss it in groups to find solutions to problems and the results are presented in front. 3) Assessment of attitude competency is carried out by the teacher by observing students' behavior in the classroom or outside the classroom. knowledge competence with written test after the end of the learning material. Assessment of skills competencies conducted by the teacher during the learning process.